Choroid Plexus Papilloma with Dandy Walker Variant: Co-existence or Association- A Case Report (Bangladesh Medical Journal, 2019)
Choroid plexus tumors are rare intracranial tumors which account for 0.4-0.6% of all brain tumors. Choroid plexus tumors represent a spectrum of neoplasms derived from papillary epithelium of normal choroid plexus, including well-differentiated papilloma (WHO grade I), intermediate form as atypical Choroid Plexus Papilloma (WHO grade II) and highly aggressive choroid plexus carcinomas (WHO grade III). Though rare, it is responsible for the communicating hydrocephalus in children due to overproduction of cerebrospinal fluid. Due to advances in molecular biology and better understanding of the tumorigenesis of choroid plexus papilloma, now it is established that several genetic syndromes and central nervous sytem abnormalities are associated with this tumor. Here, we reported a case of a 10 months old child who presented with sudden deterioration of consciousness level and after thorough evaluation, diagnosed as a case of Choroid Plexus Papilloma with Dandy Walker Variant. Till date, this is the first reported case of the association/ co-existence of such two conditions which needs further evaluation.Bangladesh Med J. 2017 May; 46 (2): 61-65